1979
DOI: 10.1037/0096-1523.5.4.639
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the acoustic startle reflex in humans in the absence of anticipatory changes in the middle ear reflex.

Abstract: If a weak tone precedes an intense tone, then the acoustic startle eyeblink reflex elicited by the stronger stimulus is inhibited. It has been suggested that the leading stimulus gives rise to a protective middle ear reflex that attenuates the effective intensity of the second. This hypothesis was tested and disproved. In seven subjects intense tone bursts sufficient to elicit both intratympanic and eyeblink responses were presented sometimes alone and sometimes preceded at various lead times (25 to 400 msec) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Groves, Boyle, Welker, and Miller (1974) provided evidence that, although indirect, favored the intratympanic hypothesis. More recent work has measured that reflex directly and has shown that it is not involved (Ison, Reiter, & Warren, 1979).…”
Section: Prepulses That Modify Reflexes Need Not Be Intense Enough T...mentioning
confidence: 99%
“…Groves, Boyle, Welker, and Miller (1974) provided evidence that, although indirect, favored the intratympanic hypothesis. More recent work has measured that reflex directly and has shown that it is not involved (Ison, Reiter, & Warren, 1979).…”
Section: Prepulses That Modify Reflexes Need Not Be Intense Enough T...mentioning
confidence: 99%